Pengaruh Beban Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai dengan Kepuasan Kerja Sebagai Variabel Intervening: Studi Kasus pada Dinas Kesehatan Provinsi Kalimantan Utara - Jomeidawathy; Ida Ariyani; Ami Pujiwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the effect of Workload, Work Discipline on Employee Performance with Job Satisfaction as an Intervening Variable (Study at the North Kalimantan Provincial Health Office). This study aims to analyze the effect of workload in the organization on employee performance, work discipline in the organization on employee performance, and analyze the effect of workload and work discipline on personnel performance mediated by job satisfaction. The sample of this study was employees of the North Kalimantan Provincial Health Office. The sampling technique in this study used purposive sampling technique using the Hair formula and data collection was carried out by providing questionnaires in the form of google forms. The samples collected were 100 respondents. The analysis technique used to analyze the data obtained was the Partial Leat Square (PLS) technique using Smart PLS software. From the results of hypothesis testing, there are several conclusions in this study, namely, there is a significant influence between workload and job satisfaction so that Hypothesis 1 (H1) is accepted. There is a significant influence between work discipline and job satisfaction so that Hypothesis 2 (H2) is accepted. There is a significant influence between job satisfaction and employee performance so that Hypothesis 3 (H3) is accepted. There is no influence between workload variables and employee performance so that Hypothesis 4 (H4) is rejected. There is a significant influence between work discipline and employee performance so that Hypothesis 5 (H5) is accepted. Workload does not have a significant effect on employee performance through employee job satisfaction so that Hypothesis 6 (H6) is rejected. Work discipline has a significant effect on employee performance through employee job satisfaction at the North Kalimantan Provincial Health Office so that Hypothesis 7 (H7) is accepted and job satisfaction can mediate work discipline on employee performance at the North Kalimantan Provincial Health Office.